ACTIVITIES OF PROPAGANDA DEPARTMENTS IN THE DISSEMINATION OF THE IDEOLOGY OF ATHEISM AMONG THE PUBLIC MASSES (1953-1956) (E Conference Zone, 2022)
The article discusses the propaganda of the ideology of atheism of the Soviet government in Uzbekistan, separate views of the political processes of the activities of the department of propaganda and agitation of the Soviet government and cultural and educational work among women